2022
DOI: 10.3233/jnd-210776
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Deflazacort and Prednisone in Duchenne Muscular Dystrophy

Abstract: Abstract. Deflazacort and prednisone/prednisolone are the current standard of care for patients with Duchenne muscular dystrophy (DMD) based on evidence that they improve muscle strength, improve timed motor function, delay loss of ambulation, improve pulmonary function, reduce the need for scoliosis surgery, delay onset of cardiomyopathy, and increase survival. Both have been used off-label for many years (choice dependent on patient preference, cost, and geographic location) before FDA approval of deflazacor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 60 publications
1
19
0
4
Order By: Relevance
“…A greater share of deflazacort- than prednisone-treated patients were on daily regimens (95.0% vs. 41.4%) and received a higher mean dose (0.61 [SD: 0.22] vs. 0.39 [0.20] mg/kg). Among the subgroup of patients on daily steroids ( n = 50), the average daily dose remained higher for deflazacort (0.61 [SD: 0.22] mg/kg/day, equivalent to 68.2% [ 24.8% ] of the recommended daily dose; n = 38) relative to prednisone (0.27 [0.16] mg/kg/day, equivalent to 36.4% [ 21.0% ] of the recommended daily dose; n = 12) (data not shown). Patients were followed for an average of 21.4 months after index, with deflazacort patients followed for a slightly shorter time relative to others (17.4 vs. 25.9 [prednisone] and 23.1 months [no steroids]) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater share of deflazacort- than prednisone-treated patients were on daily regimens (95.0% vs. 41.4%) and received a higher mean dose (0.61 [SD: 0.22] vs. 0.39 [0.20] mg/kg). Among the subgroup of patients on daily steroids ( n = 50), the average daily dose remained higher for deflazacort (0.61 [SD: 0.22] mg/kg/day, equivalent to 68.2% [ 24.8% ] of the recommended daily dose; n = 38) relative to prednisone (0.27 [0.16] mg/kg/day, equivalent to 36.4% [ 21.0% ] of the recommended daily dose; n = 12) (data not shown). Patients were followed for an average of 21.4 months after index, with deflazacort patients followed for a slightly shorter time relative to others (17.4 vs. 25.9 [prednisone] and 23.1 months [no steroids]) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The AAN guidelines classify a greater share of prednisone's efficacy evidence as Level B ("probably" effective) than Level C ("possibly" effective) [11] compared to deflazacort, but a 2016 Cochrane Review considered the quality of comparative evidence to be low [20]. More recent studies have suggested that relative to patients treated with prednisone, patients treated with deflazacort experience similar or slower rates of functional decline and different side effects [21]. A meta-analysis of placebo arm data from phase III trials found that functional decline over 48 weeks was significantly slower for deflazacort versus prednisone for five measures of ambulatory function and comparable for a sixth measure [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is uncertainty regarding the long‐term benefits and safety of these treatments. Results from randomized controlled studies revealed that side effects including sudden weight gain, confusion, depression, growth‐related complication, and cataracts may be caused by both DFZ and PRED (Matthews et al , 2016; Biggar et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals were assessed every 6-12 months by clinicians and physiotherapists specialized in neuromuscular diseases. Clinical notes were reviewed to collect demographic, genetic, treatment [4,5,[22][23][24], functional abilities (Egen Klassifikation [EK] scale version 2) [25][26][27], respiratory and cardiac data [28]. The inclusion criteria were (i) males genetically diagnosed with DMD ≥16 years old at last assessment (LA) and (ii) ambulant or nonambulant at LA.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%